T103. Komendantin rakennuksen kellari T103 länsiseinä, ovi T104:ään - Welin
sisällön kuvaus: kts. länteen
Keywords: Suomi, Savonlinna, Olavinlinna, Savonlinna, Olavinlinna, Olavinlinna T Uusi esilinna, Olavinlinna T103 Kellari; Olavinlinna